Determinants of Nordic Stakeholder Bank Performance During and After the Financial Crisis - Dolk, Julius (My University, 2019)
Stakeholder banking is an umbrella terms that is used to describe cooperative and savings banks. They differ from other commercial mainly through their ownership form, as they are owned by their customers. Because of this unique characteristic stakeholder banks are not able to use the capital markets to fund their business. Furthermore, they are often considered to run their business with a focus on stakeholder surplus maximization rather than pure profit maximization. These factors highly affect their business model, business capitalization, and risk taking. Owners, with their simultaneous role as customers, are reluctant to allow the bank to take risky positions in their operations with the fear of losing their savings. This thesis focuses on how stakeholder banks differ from their shareholder bank counterparts in the Nordic countries during and after the period of the most recent financial crisis. The effect of being a stakeholder bank, as well as differences in the micro- and macroeconomic performance determinants of the two groups, is examined through three performance variables: profitability, cost efficiency, and loan quality. This study finds stakeholder banks to be more profitable and cost efficient than shareholder banks during the crisis, as well as having better quality loans in the post-crisis period.
Keywords: stakeholder banking, bank performance, financial crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance